Ecoregional research in sub-humid West Africa - Smith, Jimmy W. (International Livestock Research Institute, 1999)
There are diverse opinions as to what an ecoregional research approach should involve. Ecoregional research is meant to fill gaps in natural resources management research, rationalise overlapping mandates, provide focal points and streamline interactions between NARS (National Agricultural Research Systems) and CGIAR (Consultative Group on International Agricultural Research) centres. This paper describes the institutional structure and technical operation of the proposed ecoregional programme in sub-humid West Africa. It shows the benchmark sites, pilot areas and working groups and elucidates ILRI's research focuses within the programme.